Pengaruh Gaya Hidup dan Konsep Diri terhadap Loyalitas Merek pada Pengguna iPhone di Samarinda - Muhammad Dhiaul Hak Nur; Marsha Anindita; Istimaroh Istimaroh (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on the influence of Lifestyle and Self-Concept on Brand Loyalty, using iPhone users in Samarinda as the study subjects. The variables examined include Lifestyle (independent variable), Self-Concept (independent variable), and Brand Loyalty (dependent variable). The research method used is quantitative with a survey approach, which allows for the collection of structured data. The sample consists of 99 respondents who are users of the iPhone brand. Data was collected through a questionnaire using a Likert scale to measure respondents’ perceptions. Data analysis was carried out using the SPSS (Statistical Product and Service Solutions) application. This study aims to provide deeper insights into brand loyalty in relation to the lifestyle and self-concept of iPhone users in Samarinda.